EFEKTIVITAS PENGELOLAAN KAS KECIL SEMESTER I TAHUN 2021 GUNA MENDUKUNG KELANCARAAN KEGIATAN BIDANG ADMINISTRASI PADA PT. INDONESIA POWER - Purnama, Martina Wulan; Pakpahan, Dewi Rafiah; Juliansyah, Roni (Jurnal Mahkota Bisnis (Makbis), 2025)
Effectiveness is a condition that states success in carrying out an activity to achieve predetermined goals. In a company, petty cash has an important role in operational activities, to find out about the application of petty cash accounting at PT. Indonesia Power, the Company's main business activities currently focus on providing electricity through electricity generation and as a provider of operation and maintenance services for power plants that operate power plants spread across Indonesia. In daily petty cash operational activities, a fixed fund system method is used. The type of research used is qualitative descriptive analysis. Petty cash funds are usually available in every company, this is because many small needs are impractical if paid by check. Likewise with PT. Indonesia Power.